(untitled) (Journal of Partial Differential Equations, 2020)
Results concerning existence, uniqueness and local regularity of Inhomogeneous Schrödinger flow from T^d_R into S^2, are presented by using the difference method, where T^d_R=R^d/(R·Z)^d.